Konstruksi Sosial Masyarakat Dusun Pancer Terhadap Kawasan Konservasi Pantai Cemara Sebagai Bentuk Mitigasi Bencana - Putri Ayu Pratna Paramita (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2023)
The tsunami disaster that hit Pancer hamlet in 1994 created dark memories for the community. The people of Pancer hamlet seem to have forgotten about the historical traces of this devastating natural disaster. Awareness of disaster mitigation in society is increasingly fading. This made various parties concerned about the possibility of future disasters so that a conservation area was created as a preventive measure. This research is an ethnographic research with a qualitative research approach. Informants were determined by purposive sampling or directly selected by the researcher. Furthermore, in data collection techniques, researchers used three data collection techniques including observation, interviews, and documentation. The researcher uses Peter L. Berger's theory of social construction as an analytical tool. The results of the study explained that there were concrete actions by conserving pine trees on the shoreline which were carried out by KUB Sekar Arum in disaster mitigation efforts. The institution always tries to make the surrounding community aware, provide examples, and socialize related to disaster mitigation efforts through pine tree conservation. The occurrence of externalization, objectivation, and internalization actions shows the formation of social construction in the community related to disaster mitigation efforts through conservation areas which are embodied in the KUB Sekar Arum.